Pengaruh Kepuasan Kerja Terhadap Kedisiplinan Karyawan Pada PT. Ramayana Lestari Sentosa, Tbk Palembang - Efrina, Efrina (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2019)
The problem formulation in this writing of this study is how influence of satisfaction work to the discipline of labour at PT. Ramayana Lestari Sentosa, Tbk Palembang The purpose of this research to know the analyze influence of satisfaction work to the discipline of labour at PT. Ramayana Lestari Sentosa, Tbk Palembang. This research conducted at PT. Ramayana Lestari Sentosa, Tbk Palembang which is address on Jalan Radial Komplek Ilir Barat Permai Blok D3 Palembang. This research used assosiative research which purpose to know relation between two variable or more, the data used in this study were primary and secondary data. The technique of collecting data used in this study was questionnaire and documentation, the method of analysis used were qualitative and quantitative analysis. Based on the analysis result, it showed that the satisfaction work has positive influence to discipline of labour , it meant if there was increase of satisfaction work will follow the discipline of labour, on the contrary if there was decrease of satisfaction work will follow the decrease of the discipline of labour.